If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (-3x + -1) = 1 Reorder the terms: 2x + (-1 + -3x) = 1 Remove parenthesis around (-1 + -3x) 2x + -1 + -3x = 1 Reorder the terms: -1 + 2x + -3x = 1 Combine like terms: 2x + -3x = -1x -1 + -1x = 1 Solving -1 + -1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 1 + 1 -1x = 1 + 1 Combine like terms: 1 + 1 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 5x*x+8x+7x*x+6x= | | 1/3x=18 | | x/4-3=x/2+1 | | X*y/z | | .07x+.11y=182.40 | | x/4-3+x/2+1 | | 38q=5 | | 8m=6.4 | | x^6=79 | | 22/25*15/52*8/33 | | 0.9(8x+16)=1.7-(x+2) | | 12x-89=81+2x | | 5x+x*x+2x+5-4-x*x= | | 9k-5k+5=17 | | w-12=-0.6w | | -169/(-1.3) | | 1/x=0.2/8 | | 2x+4y=224 | | x^3+3x^2=5 | | kx-2y+9=0 | | 8/9d=5/6 | | 13000+25000x=27500 | | x^2-5+41=0 | | 8x+24y= | | 7m^2+11m-6=0 | | x^2-3+41=0 | | 3(x+4)=x+6-2 | | (x+10)5=100 | | x^2/2+5/2x=2 | | -5+4=-3 | | x^2-4+41=0 | | x+1/3=7/9 |